Pengaruh Self Efficacy, Motivasi dan Komitmen Organisasional Terhadap Kinerja Pegawai Pada Dinas Ketahanan Pangan, Pertanian dan Perikanan Kota Probolinggo - Rahmawati, Lisa; Ngatimun, Ngatimun; Vidiyastutik, Elok Dwi (JUMAD : Journal Management, Accounting, & Digital Business, 2024)
This research was conducted at the Probolinggo City Food Security, Agriculture and Fisheries Service. The aim of this research is to determine the influence of self-efficacy, motivation and organizational commitment on employee performance at the Probolinggo City Food Security, Agriculture and Fisheries Service. The type of research used is quantitative research. The sample in this research used a purposive sampling technique. Sugiyono (2018) Purposive sampling is a technique for determining samples with certain considerations. In this study, 76 people were selected as a sample consisting of ASN and non-ASN. Data was collected through questionnaires. In proving or analyzing this, we use validity and reliability tests, classical assumption tests, multiple regression analysis, coefficient of determination (R2) and hypothesis testing. The research results show that the influence of Self Efficacy (X1), Motivation (X2) and Organizational Commitment (X3) has a partially significant effect on Employee Performance (Y). Keywords: Self Efficacy, Motivation, Organizational Commitment, Employee Performance